TRANSIENT LAMINAR SEPARATED FLOW AROUND AN IMPULSIVELY STARTED SPHERICAL PARTICLE AT 20≤RE≤1000 (Journal of Sciences & Technology, 2021)
Numerical simulations of the axisymmetric laminar flow characteristics past a rigid sphere impulsively started are presented for Reynolds numbers from 20 to 1000. The results are obtained by solving the complete time dependant Navier-Stokes equations in vorticity and stream function formulation. A fourth order compact method is used to discretize the Poisson equation of stream function while the vorticity transport equation is solved by an alternating direction implicit method. Time evolution of flow separation angle and length of the vortex behind the sphere are reported. Time variation of the axial velocity in the vortex and the wall vorticity around the sphere are also examined. Secondary vortices are seen to be initiated at Reynolds number of 610 and for dimensionless time t about 5. Comparisons with previously published simulations and experimental data for steady state conditions show very good agreement.